L’expérience professionnelle au prisme du rapport de genre - Louis-Marie Barnier (Cahiers de la Recherche sur l'Education et les Savoirs)
Knowledge and experience are inscribed within the double social relation of, work and gender. The value placed upon experience appears as the result of a social relationship that ranks different activities, such as knowledge and experiences and, within the latter, classifies different types of experience. The skills acquired by women in jobs that pertain to the “feminine sphere” (check-in staff and cabin crew) are devalued. This is due to the fact that these jobs are not based on a trade structured around a specific body of knowledge and/or a noble object (i.e. the plane, as is the case for the ‘masculine’ occupations of pilots and mechanics studied here). On the contrary, the working situations hinge around a devalued object, the human being, for whom are organised fragmented tasks given to women because of the gendered division of labour.